2021
DOI: 10.3390/ijms222111626
|View full text |Cite
|
Sign up to set email alerts
|

Clustered Regularly Interspaced Short Palindromic Repeat Analysis of Clonal Complex 17 Serotype III Group B Streptococcus Strains Causing Neonatal Invasive Diseases

Abstract: Group B Streptococcus (GBS) is an important pathogen of neonatal infections, and the clonal complex (CC)-17/serotype III GBS strain has emerged as the dominant strain. The clinical manifestations of CC17/III GBS sepsis may vary greatly but have not been well-investigated. A total of 103 CC17/III GBS isolates that caused neonatal invasive diseases were studied using a new approach based on clustered regularly interspaced short palindromic repeats (CRISPR) loci and restriction fragment length polymorphism (RFLP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…ALP family proteins are commonly expressed virulence factors in GBS that are also associated with immune evasion (Paoletti and Kasper, 2019;Lin L. et al, 2021). This family of proteins includes ALP-C, ALP-1, ALP-2, ALP-3, ALP-4, and Rib, encoded by the genes bca, alp1, alp2, alp3, alp4, and rib, respectively, and their amino acid sequences exhibit homology (Furfaro et al, 2018).…”
Section: Bacterial Immune Evasion Related Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALP family proteins are commonly expressed virulence factors in GBS that are also associated with immune evasion (Paoletti and Kasper, 2019;Lin L. et al, 2021). This family of proteins includes ALP-C, ALP-1, ALP-2, ALP-3, ALP-4, and Rib, encoded by the genes bca, alp1, alp2, alp3, alp4, and rib, respectively, and their amino acid sequences exhibit homology (Furfaro et al, 2018).…”
Section: Bacterial Immune Evasion Related Virulence Factorsmentioning
confidence: 99%
“…Currently, there is limited understanding of the pathogenesis of late-onset GBS infection ( Delara et al, 2023 ), which may be related to vertical transmission, nosocomial infection, or community-acquired infection. Serotype III GBS is highly associated with meningitis ( Hsu et al, 2021 ). Recent studies have shown that preterm birth is a major risk factor for late-onset GBS infection ( Gonçalves et al, 2022 ; Choi et al, 2023 ; Paul et al, 2023 ).…”
Section: Gbs Related Clinical Diseases In Obstetrics and Gynecologymentioning
confidence: 99%
“…When dCas binds to the promoter or transcription start site of the target gene, it can prevent the initiation of transcription. When dCas binds to the target gene open reading frame, it prevents the binding of RNA polymerases and transcription factors, thereby inhibiting transcription [ 46 ].…”
Section: Crispr/cas9-based Gene-editing Toolsmentioning
confidence: 99%
“…Ma et al successfully reduced the amylose content of rice grains from 14.6% to 2.6% by knocking out the WAXY ( Wx ) gene, thereby obtaining waxy rice mutant plants [ 25 ]. Similarly, the maize Wx1 gene encodes a starch synthase affecting the grain composition [ 46 ]. Knocking out Wx1 via the CRISPR/Cas9 system can increase the amylopectin content of maize grains to almost 100% [ 47 ], without inducing other phenotypic changes.…”
Section: Application Of the Crispr/cas9 System For Crop Breedingmentioning
confidence: 99%
“…Streptococcus agalactiae identification is a challenge for modern microbiological diagnostics, especially taking into account the phenotypic and molecular diversity of the strains belonging to this species [7][8][9][10]. Moreover, in recent years, an increase in GBS resistance to selected drugs has been observed [11].…”
Section: Introductionmentioning
confidence: 99%